Case report on anti-GQ1b antibody syndrome: initial symptoms of pupil palsy and periorbital pain - Du, Yang; Wang, Weidong; Zhang, Lili; Li, Yuan; Chen, Xiang; Yang, Hui; Ding, Xin (Frontiers in Immunology, 2024)
Anti-GQ1b antibody syndrome is a spectrum of autoimmune disorders affecting nervous systems. We report a case of a 53-year-old woman presenting mydriasis with acute onset of periorbital pain, photophobia, and subsequently, diplopia. Despite weakly positive anti-GQ1b IgG antibody, the patient exhibited atypical features with isolated ophthalmoplegia and absence of classic Miller-Fisher syndrome triad. Symptoms improved spontaneously without specific immunotherapy. This case highlights the variable clinical presentations of anti-GQ1b antibody syndrome, emphasizing the importance of considering this diagnosis in patients with unexplained iris abnormalities and ophthalmoplegia.